Realojamento da pobreza : interface da segregação socioespacial na produção da cidade de Maringá à luz conceitual marxista do valor-de-troca - Reis, Josivaldo Souza (2017)
The present study analyzed the rehousing process of low income population groups as an interface of socio-spatial segregation and as a component of urban space production in the city of Maringá. Therefore, we start from the understanding that, contemporaneously, the urban space of Maringá has been a place par excellence of processes of social production and social reproduction and sociability, in which are correlated situations of poverty, social exclusion, socio-spatial segregation, inequalities, others. In the same way, it has also been a space in which there are various interests and social projects that, in turn, promote unequal access to low-income social groups for services and wealth socially produced by workers in the capitalist city. The analysis of this study was anchored in the conceptions of the Marxist theory of value-of-exchange, whereby we show a model of a city that has been constituting itself as a product, a functional commodity, above all for real estate capital and for producers Urban areas. In addition, through field research, with the application of questionnaires, we carried out a case study in three housing projects of the Minha Casa, Minha Vida Program, namely - Pioneiro Gonçalo Vieira dos Santos; José Israel Factori and José Pires de Oliveira Pioneer - all located in the Floriano district of Maringá. Through this research, it was possible to verify the peripherization of this population contingent to the fringes of the city, a process which we call poverty rehousing as a component of socio-spatial segregation. Supported by Marxist theory, in studying this process of rehousing poverty in Maringá, we find that this city is conceived in a commodity perspective, functional for the private interests of social agents. These, in turn, plan the city out of merely capitalist relations and interests and outweigh collective interests, so that, under this bias, the planning and the occupation of the urban space of Maringá occurs under patterns that undermine the welfare and do not provide conditions worthy of survival and collective coexistence to the segments of the society of lesser economic power, bequeathing to them for these a Herculean effort by their peripheral position, by their condition stigmatized, finally, by their condition of poverty.